High temperature oxidation behavior and wear resistance of Ti0.53Al0.47N coating by cathodic arc evaporation. (January 2017) - Wu, Z.T.; Sun, P.; Qi, Z.B.; Wei, B.B.; Wang, Z.C.
Abstract: In this study, oxidation and tribology behavior of Ti0.53 Al0.47 N coating deposited by cathodic arc evaporation were investigated. The effects of varying temperature from RT to 850 °C on microstructure, phase composition, oxidation behavior, and wear resistance of the coating were evaluated. The phase structure of the Ti0.53 Al0.47 N coating changes slightly with the elevated temperature, whereas the oxidation behavior of the coating reveals a remarkable variation due to the formation of different type oxide scales. The final oxide scale consists of an outer Al2 O3 dominated layer and an inner TiO2 dominated layer, exhibiting a bilayer structure. A serious wear of the Ti0.53 Al0.47 N coating occurs during the room temperature test. With increasing the test temperature up to 700 °C, the coating show promoted wear resistance owing to the Al2 O3 oxide scale provides an excellent protection against the wear. However, further increasing the temperature up to 850 °C produces a fast growth of the TiO2 . This deteriorates the protection of the Al2 O3 scale, resulting in an accelerated oxidation of the coating. Consequently, the Ti0.53 Al0.47 N coating illustrates a degraded wear resistance at 850 °C. Highlights: High-temperature wear tests of the Ti0.53 Al0.47 N coatings were carried out. The maximum test temperature was elevated to 850 °C during the wear test. XPS analysis and AES depth profiling of the oxide scales formed at RT–850 °C. Relationship between wear mechanism and working temperature was discussed.